Physical characterization of K-doped 0.9PMN-0.1PT synthesized by an association of the columbite route and the polymeric precursor method - Cavalheiro, A. A. [UNESP]; Bruno, J. C. [UNESP]; Zaghete, M. A. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2005)
The solid solution 0.9PbMg 1/3Nb 2/3O 3-0.1PbTiO 3 is one of the most widely investigated relaxor ceramic, because of its high dielectric constant and low sintering temperatures. PMN-PT powders containing single perovskite phase were prepared by using a Timodified columbite precursor obtained by the polymeric precursor method. Such precursor reacts directly with stoichiometric amount of PbO to obtain pyrochlore-free PMN-PT powders. The structural effects of K additive included in the columbite precursor and 0.9PMN-0.1PT powders were also studied. The phase formation at each processing step was verified by XRD analysis, being these results used for the structural refinement by the Rietveld method. It was verified the addition of K in the columbite precursor promotes a slight increasing in the powder crystallinity. There was not a decrease in the amount of perovskite phase PMN-PT for 1mol% of K, and the particle and grain size were reduced, making this additive a powerful tool for grain size control.
Keywords: Ceramics; Chemical synthesis; Columbite and rietveld method; PMN-PT; Powder crystallinity; Additives; Ceramic products; Rietveld method; Stoichiometry; Synthesis (chemical); Solid solutions